2022
DOI: 10.1097/mcc.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated AKI

Abstract: Purpose of reviewWhile it is now widely established acute kidney injury (AKI) is a common and important complication of coronavirus disease (COVID-19) disease, there is marked variability in its reported incidence and outcomes. This narrative review provides a mid-2022 summary of the latest epidemiological evidence on AKI in COVID-19.Recent findingsLarge observational studies and meta-analyses report an AKI incidence of 28–34% in all inpatients and 46–77% in intensive care unit (ICU). The incidence of more sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
5

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 71 publications
1
21
0
5
Order By: Relevance
“…Our results for the prevalence of AKI (30% overall, 52.1% in ICU patients), odds of mortality (3.5 times higher for AKI vs no AKI), and mean LOS (11.9 days) are consistent with prior studies that extend past the first few months of the pandemic. 11,23 Recent reviews and meta-analyses that include many studies of the early pandemic period reported the following ranges: 28% to 34% 11,14,15,40 prevalence of overall AKI, 46% to 77% prevalence of AKI in ICU patients, 11,14,40 and 2.55 to 23.09 for OR for mortality. 41 Furthermore, in a study of AKI in COVID patients during all of 2020, HR (95% CI) for mortality was 3.8 (3.24-4.45), and mean LOS was 10.4 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results for the prevalence of AKI (30% overall, 52.1% in ICU patients), odds of mortality (3.5 times higher for AKI vs no AKI), and mean LOS (11.9 days) are consistent with prior studies that extend past the first few months of the pandemic. 11,23 Recent reviews and meta-analyses that include many studies of the early pandemic period reported the following ranges: 28% to 34% 11,14,15,40 prevalence of overall AKI, 46% to 77% prevalence of AKI in ICU patients, 11,14,40 and 2.55 to 23.09 for OR for mortality. 41 Furthermore, in a study of AKI in COVID patients during all of 2020, HR (95% CI) for mortality was 3.8 (3.24-4.45), and mean LOS was 10.4 days.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 JOURNAL OF HEALTH ECONOMICS AND OUTCOMES RESEARCH AKI is now known to be a common complication of COVID-19, but it is unclear whether COVID-19 affects the kidneys directly, or indirectly, by causing more severe illness, similar to other severe infections. 11 AKI may be more frequent and more severe (ie, more stage 3 AKI) in hospitalized patients with than without COVID-19, and is associated with 7 to 15 times higher mortality risk vs COVID-19 patients without AKI. [12][13][14][15] Furthermore, in patients without COVID-19, AKI that first occurs in the hospital (hospital-acquired AKI [HA-AKI]) is associated with higher mortality, 16 longer hospital length of stay (LOS), and higher costs 17 than community-acquired AKI (CA-AKI), which occurs prior to hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of AKI was also associated with mortality [ 24 ]. Similarly, the incidence of more severe AKI that requires renal-replacement therapy in an ICU appears to have declined over time: the data from England and Wales show that RRT declined from 26% at the start of the pandemic to 14% in 2022 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) may be caused by many factors, including heart failure, sepsis, hemorrhage, nephro-toxic drugs, as well as by COVID-19. A recent review paper addressed COVID-19-associated AKI [ 5 ]. It is now widely believed that AKI is a frequent and significant complication of COVID-19; however, there is significant variability in its reported incidence and outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation